Evaluation of the Cerebrospinal Fluid Flow Dynamics with Microvascular Imaging Ultrasound in Infants - Luis Octavio Tierradentro-Garcia; Levy Onyango; Rebecca Dennis; Colbey W. Freeman; Sophie Haddad; Brandi Kozak; Misun Hwang (MDPI AG, 2023)
Purpose: Microvascular imaging ultrasound (MVI) can detect slow blood flow in small-caliber cerebral vessels. This technology may help assess flow in other intracranial structures, such as the ventricular system. In this study, we describe the use of MVI for characterizing intraventricular cerebrospinal fluid (CSF) flow dynamics in infants. Materials and methods: We included infants with brain ultrasound that had MVI B-Flow cine clips in the sagittal plane. Two blinded reviewers examined the images, dictated a diagnostic impression, and identified the third ventricle, cerebral aqueduct, fourth ventricle, and CSF flow direction. A third reviewer evaluated the discrepancies. We evaluated the association of visualization of CSF flow as detectable with MVI, with the diagnostic impressions. We also assessed the inter-rater reliability (IRR) for detecting CSF flow. Results: We evaluated 101 infants, mean age 40 ± 53 days. Based on brain MVI B-Flow, a total of 49 patients had normal brain US scans, 40 had hydrocephalus, 26 had intraventricular hemorrhage (IVH), and 14 had hydrocephalus+IVH. Using spatially moving MVI signal in the third ventricle, cerebral aqueduct, and fourth ventricle as the criteria for CSF flow, CSF flow was identified in 10.9% (n = 11), 15.8% (n = 16), and 16.8% (n = 17) of cases, respectively. Flow direction was detected in 19.8% (n = 20) of cases; 70% (n = 14) was caudocranial, 15% (n = 3) was craniocaudal, and 15% (n = 3) bidirectional, with IRR = 0.662, p < 0.001. Visualization of CSF flow was significantly associated with the presence of IVH alone (OR 9.7 [3.3-29.0], p < 0.001) and IVH+hydrocephalus (OR 12.4 [3.5-440], p < 0.001), but not with hydrocephalus alone (p = 0.116). Conclusion: This study demonstrates that MVI can detect CSF flow dynamics in infants with a history of post-hemorrhagic hydrocephalus with a high IRR.